Representasi Sipil-Militer dan Konstruksi Maskulinitas pada Film Jenderal Soedirman (2015) - Budiman, Hary Ganjar; Sofianto, Kunto (Paradigma: Jurnal Kajian Budaya, 2018)
Jenderal Soedirman (2015) is a historical film that reveals the story of General Soedirman during the guerrilla war to maintain the Indonesia’s independence. The film was sponsored directly by the army (Kartika Eka Paksi Foundation and TNI) and involved the army in its making process. Therefore, the historical representation of this film is a history from the army’s point of view. Referring to Gramsci, a film can be seen as a hegemonic apparatus that contributes to the process of negotiating the interests of dominant groups. This study attempted to elaborate such representations of civil-military relationships and masculinity construction contained in Jenderal Soedirman. It used a qualitative approach and employed the encoding/decoding paradigm proposed by Stuart Hall. The results showed that the civil-military relationships in this film were mostly dominated by military roles. Masculinity in this film was formed by combining the concept of “Kiai” (Muslim clerics) and military patriotism wrapped in Islamic expressions.